"Distance" in intellectual property protection and MNEs' foreign subsidiary innovation performance. Issue 4 (24th March 2022) - Konara, Palitha; Batsakis, Georgios; Shirodkar, Vikrant
Abstract: Drawing on the institution‐based view of intellectual property (IP) rights, we argue that "distance" in IP protection strength of MNEs' home and host countries reduces the ability of MNEs to innovate at foreign subsidiary locations. We contend that this logic applies in both directions—i.e., (1) downward direction, when MNEs originating from stronger IP protection regimes innovate in weaker IP protection regimes, and (2) upward direction, when MNEs originating from weaker IP protection regimes innovate in stronger IP protection regimes. Furthermore, we suggest that the negative effect of IP protection distance on foreign subsidiary innovation performance will be moderated by internal (strategic) and external (institutional) conditions, such as the subsidiary experience, subsidiary ownership type (full vs. partial), cultural distance and the extent of scientific labor in the host country. We test the above relationships using a very large panel data set consisting of MNE subsidiary‐level data in the manufacturing industry for 15, 246 subsidiaries of 11, 284 parent firms, representing 47 home countries and 31 host countries and covering a total of 91, 347 observations for the period 2005–2013. Our findings show that (1) the adverse effect of IP protection distance on subsidiary innovation performance applies in both directions; (2) the effect is more intense in case of the downward direction; and (3) the moderating effects vary depending on the direction of IP protection distance.